2016 IEEE International Symposium on Information Theory (ISIT) 2016
DOI: 10.1109/isit.2016.7541342
|View full text |Cite
|
Sign up to set email alerts
|

Finite blocklength achievable rates for energy harvesting AWGN channels with infinite buffer

Abstract: Abstract-We consider an additive white Gaussian channel where the transmitter is powered by an energy harvesting source. For such a system, we provide a lower bound on the maximal codebook at finite code lengths that improves upon previously known bounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…1] are equal to the capacity, −c 1 log n n and −c 2 2+ε nε respectively where c 1 and c 2 are some positive constants that do not depend on n and ε. Subsequently, Shenoy and Sharma [16] refined the analysis in [15] and improved the second-order term to − c3 √ nε where c 3 is some positive constant that does not depend on n and ε. This paper further improves the second-order term to −c 4 log(1/ε) n for any ε ∈ (0, 1/2) where c 4 is some positive constant that does not depend on n and ε (see Remark 2).…”
Section: B Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…1] are equal to the capacity, −c 1 log n n and −c 2 2+ε nε respectively where c 1 and c 2 are some positive constants that do not depend on n and ε. Subsequently, Shenoy and Sharma [16] refined the analysis in [15] and improved the second-order term to − c3 √ nε where c 3 is some positive constant that does not depend on n and ε. This paper further improves the second-order term to −c 4 log(1/ε) n for any ε ∈ (0, 1/2) where c 4 is some positive constant that does not depend on n and ε (see Remark 2).…”
Section: B Related Workmentioning
confidence: 99%
“…For any (n, M )-code defined on the AWGN EH channel, let p W,E n ,X n ,Y n ,Ŵ be the joint distribution induced by the code. We can use Definition 1, (14) and (16) to factorize p W,E n ,X n ,Y n ,Ŵ as follows:…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Shenoy and Sharma [16] refined the analysis in [15] and improved the second-order term to − c3 √ nε where c 3 is some positive constant that does not depend on n and ε.…”
Section: B Related Workmentioning
confidence: 99%
“…Only recently, scenarios with EH have been analyzed at finite blocklength regime [19]- [23]. In [20] the authors consider an AWGN channel where the transmitter is powered by EH only. Then, a lower bound on the maximal codebook at finite code lengths is provided and shown that it improves upon previously known bounds.…”
Section: Introductionmentioning
confidence: 99%